Ancient plants and people : contemporary trends in archaeobotany - Madella, Marco; Lancelotti, Carla; Savard, Manon, 1970- (The University of Arizona Press, 2014)
"Ancient Plants and People is a timely discussion of the global perspectives on archaeobotany and the rich harvest of knowledge it yields. Contributors examine the importance of plants to human culture over time and geographic regions and what it teaches of humans, their culture, and their landscapes"--Provided by publisher